Case Study on Energy Strategy Concerning Santa Ana Wind Activity Triggering Fires in Southern California - Evan, Bah; Al Huda, Luqman; Dianisa Khoirum Sandi; Yusuf Dewantoro Herlambang; Eri Prihatmini; Vita Ayu Aspriyanti (Politeknik Negeri Semarang, 2024)
Santa Ana winds, which are characterized by their scorching, arid, and forceful surges, significantly exacerbate wildfire hazards in Southern California, extending to 23,000 ha, particularly in the Los Angeles region. The purpose of this study is to examine the correlation between anthropogenic influences and natural climatic phenomena, with a specific focus on the influence of regional energy policies on the frequency and intensity of wildfires. The interaction between the Santa Ana winds and landscapes that are becoming more flammable has become more intensive in recent decades, although they are a natural phenomenon. Inadequately regulated urban expansion, prolonged droughts, and elevated temperatures are the causes of this intensification. Utility companies explicitly link wildfire ignitions during wind events to their energy infrastructure, particularly above-ground power lines. Moreover, the crisis has been further exacerbated by inadequate utility modernization, delayed policy reforms, and limited investment in fire-resilient infrastructure. This study assesses the degree to which regulatory inertia and climate change interact to elevate the likelihood of wildfires by analyzing historical wildfire data, meteorological patterns, and the evolution of California's energy policies. In the face of escalating climatic extremes, the results underscore the urgent need for energy strategies that are forward-thinking and integrated and that prioritize environmental sustainability, conflagration prevention, and resilience.